Caffeine prevents LPS-induced inflammatory responses in RAW264.7 cells and zebrafish. (25th March 2016) - Hwang, Ji-Hyun; Kim, Kui-Jin; Ryu, Su-Jung; Lee, Boo-Yong
Abstract: Caffeine is a white crystalline xanthine alkaloid found in the seeds of coffee plants and leaves of the tea bush. In this study, we evaluated whether caffeine exerts anti-inflammatory effects on lipopolysaccharide (LPS)-induced inflammation both in vitro and in vivo . RAW264.7 cells were treated with various concentrations of caffeine in the presence or absence of LPS. Caffeine decreased the LPS-induced inflammatory mediator, nitric oxide (NO). Caffeine treatment also reduced the expression of pro-inflammatory genes, including inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), interleukin (IL)-3, IL-6 and IL-12, and decreased both IL-6 secretion and phosphorylated p38MAPK expression in LPS-treated RAW264.7 cells. Caffeine inhibited nuclear translocation of nuclear factor κB (NF-κB) via IκBα phosphorylation. In addition, caffeine inhibited LPS-induced NO production in zebrafish. These results suggest that caffeine may suppress LPS-induced inflammatory responses in RAW264.7 cells by regulating NF-κB activation and MAPK phosphorylation. Highlights: Caffeine inhibits LPS-induced pro-inflammatory factor by regulating gene expression in RAW264.7 cells. Caffeine regulates NF-κB activation and phosphorylation of MAPKs. Caffeine suppresses LPS-induced NO production by using DCF-FM DA in zebrafish.